(3JaSjQ dZR bCHhS Ydi WQjb GdESJKeGQs - (3YHO Gddg Hf GdWjH GdHZOGOj , nCoHh GdnanQL GHf GdpqWpqjH , J (B435 (3g` s
(3ChdgG (B:s
(3YQV dZR bGHhS JUhjQ GdOfjG hhLg eONd GdEfSGf EdjgG hJUQag ajgG heNQLg efgG EPG cGf SYjOkG s
(3BNQgG (B:s
(3JeJ KeQI GddZR hGdMeO ddg hGgH GdYbd hgh GdeYjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B14s
(3fSNI fajSI LOkGs
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(888/14) s
Keywords: (3GdadSaI hGdefWbs